2019
DOI: 10.1002/bse.2422
|View full text |Cite
|
Sign up to set email alerts
|

ISO 14001, EMAS and environmental performance: A meta‐analysis

Abstract: The adoption of voluntary environmental certifications such as ISO 14001 and Eco‐Management and Audit Scheme (EMAS) has gained momentum in the last two decades. The scholarly literature has analyzed in depth the performance implications of the adoption of these certificates. Yet the findings are scattered and inconclusive. This article aims to shed light on this issue by meta‐analyzing the influence of the adoption of voluntary environmental certifications on corporate environmental performance, drawing on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 113 publications
1
62
0
Order By: Relevance
“…Likewise, Testa et al (2014) found that big organizations obtain more benefit from the implementation of an EMS based on either ISO 14001 or EMAS rather than another type of EMS. Finally, Erauskin‐Tolosa, Zubeltzu‐Jaka, Heras‐Saizarbitoria, and Boiral (2020) performed a meta‐analysis on the link between certifiable EMSs and environmental performance drawing on a sample of 53 scholarly studies analyzing a total of 182,926 companies. Their findings showed a positive influence of ISO 14001 and EMAS certification on corporate environmental performance, but a set of underlying moderating effects were also identified; there was a pronounced positive effect of adoptions based on environmental innovation and for firms with a more mature certification.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…Likewise, Testa et al (2014) found that big organizations obtain more benefit from the implementation of an EMS based on either ISO 14001 or EMAS rather than another type of EMS. Finally, Erauskin‐Tolosa, Zubeltzu‐Jaka, Heras‐Saizarbitoria, and Boiral (2020) performed a meta‐analysis on the link between certifiable EMSs and environmental performance drawing on a sample of 53 scholarly studies analyzing a total of 182,926 companies. Their findings showed a positive influence of ISO 14001 and EMAS certification on corporate environmental performance, but a set of underlying moderating effects were also identified; there was a pronounced positive effect of adoptions based on environmental innovation and for firms with a more mature certification.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…Because the integration of the systematic framework defined by ISO 14001 is usually associated with the adoption of better environmental technologies, more rigorous organizational procedures to protect natural resources, and stronger environmental awareness among managers and employees, ISO 14001 adoption is expected to ultimately result in improved environmental performance (Curkovic & Sroufe, 2011; Erauskin‐Tolosa, Zubeltzu‐Jaka, Heras‐Saizarbitoria, & Boiral, 2020; Garrido, González, & Orcos, 2020; Molina‐Azorín, Tarí, Claver‐Cortés, & López‐Gamero, 2009; Testa et al, 2014). Accordingly, our first hypothesis proposes the following:H1 ISO 14001 adoption contributes to increased firm environmental efficiency.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Employees through their voluntary actions, like energy conservation, minimum use of stationery, using durable articles for different activities, developing a sense of environmental awareness in peers' etc. meaningfully contribute to the overall EP of the organizations (Erauskin‐Tolosa, Zubeltzu‐Jaka, Heras‐Saizarbitoria, & Boiral, 2020). Such actions on the part of employees justify our view that EEB is a major antecedent of EEP.…”
Section: Introductionmentioning
confidence: 99%